2004
DOI: 10.1002/gcc.20094
|View full text |Cite
|
Sign up to set email alerts
|

Telomere‐mediated mitotic disturbances in immortalized ovarian epithelial cells reproduce chromosomal losses and breakpoints from ovarian carcinoma

Abstract: Ovarian carcinomas (OCs) often exhibit highly complex cytogenetic changes. Abnormal chromosome segregation at mitosis is one potential mechanism for genomic rearrangements in tumors. In this study, OCs were demonstrated to have dysfunctional short telomeres, anaphase bridging, and multipolar mitoses with supernumerary centrosomes. When normal human ovarian surface epithelial (HOSE) cells were transfected with human papilloma virus 16 e6/e7 genes and subsequently driven into telomere crisis, the same set of mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…1H). Recent studies have suggested that T-CIN may also result in loss of whole chromosomes (9,28). The morphology of anaphase bridge in our panel of cell lines suggested that this could be the case also in UC because f10% to 20% of mitoses with anaphase bridge showed a complete dislocation of the bridge from one of the anaphase poles (Fig.…”
Section: Resultssupporting
confidence: 54%
“…1H). Recent studies have suggested that T-CIN may also result in loss of whole chromosomes (9,28). The morphology of anaphase bridge in our panel of cell lines suggested that this could be the case also in UC because f10% to 20% of mitoses with anaphase bridge showed a complete dislocation of the bridge from one of the anaphase poles (Fig.…”
Section: Resultssupporting
confidence: 54%
“…It has previously been shown that expression of the human papillomavirus E6 and E7 proteins in epithelial cells may trigger abnormal spindle pole formation by an abundant number of centrosomes in parallel with the occurrence of anaphase bridges (24 -26). This centrosome amplification has been shown to appear due to failure in cytokinesis, leading to formation of cells with a 2-fold amount of both chromosomes and centrosomes (26), explaining the relatively high numbers of control cells with abundant numbers of centrosomes observed.…”
Section: Discussionmentioning
confidence: 97%
“…Anaphase bridges may be generated when broken chromosomes, either induced by irradiation or triggered by abnormal shortening of the telomeres, fuse (21,26). These anaphase bridges usually are resolved by new chromosomal breakages (27).…”
Section: Discussionmentioning
confidence: 99%
“…7 Tumors with high rates of anaphase bridging (such as ovarian, head and neck tumors) are characterized by a multimodal distribution of genomic imbalances, consistent with a dramatically increased rate of chromosomal rearrangement. 8,9 Hepatocellular carcinoma (HCC) is the seventh most common cancer worldwide, accounting for the highest number of adult malignancies in areas endemic for hepatitis B virus (HBV). Telomere shortening is an early event in multistep hepatocarcinogenesis, occurring in preneoplastic lesions of dysplastic nodules 10,11 and shortened telomeres have been reported to induce chromosomal instability in hepatocytes, especially important in HBV-related hepatocarcinogenesis.…”
mentioning
confidence: 99%